Synthesis and growth mechanism of carbon-supported nanoparticle catalysts by physical vapor deposition onto a liquid medium substrate - Cha, In Young; Kim, Hyung Tae; Ahn, Minjeh; Jang, Jong Hyun; Kim, Young Gyu; Sung, Yung-Eun; Yoo, Sung Jong (ELSEVIER SCIENCE BV, 2019)
Metal nanoparticles (NPs) have been extensively investigated owing to their unique properties attributing to their high surface/bulk ratio and finite number of atoms. However, the thermodynamic instability of NPs, which originates from their finite size, limits their practical applications. Hence, carbon-supported Pt NPs are synthesized onto carbon-containing liquid substrates via direct one-step sputtering. In order to successfully produce uniform Pt NPs via sputtering using various ionic liquids as non-volatile liquid substrates, special conditions are required, and the relationship between ionic liquids and particle surfaces should be investigated. It has been reported that anions and carbon supports of ionic liquids significantly affect the dispersion and synthesis of Pt NPs. In this study, we proposed a mechanism underlying the chemical bonding between anions and carbon supports and verified it using X-ray photoelectron spectroscopy and infrared spectroscopy.
Keywords: IONIC LIQUID; PHYSICOCHEMICAL PROPERTIES; PALLADIUM NANOPARTICLES; SPUTTER-DEPOSITION; GOLD NANOPARTICLES; PLATINUM